PSYCHOLOGICAL CHARACTERISTICS OF PERSONALITY IN TEACHING FORMATION PROCESS CONTROL OBJECT COMPETENCIES OF BASIC TRAINING - Ладогубець, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article it’s examined the psychological and pedagogical aspects of the formation of subject competencies fundamental training bachelors higher technical school, taking into account the limitations of subjective action of the teacher on the measurement results on the one hand, and taking into account the definitions and psychophysiological features of the personality of each student on the other side. Proposed certain quality control fundamental training bachelors depending on the psycho-physiological characteristics of the individual ’s degree